Assessment of the intensive phase ‘Shakti Divas’ initiative to combatting anemia in Rajasthan, India - Nitin Kumar Joshi; Pankaj Bhardwaj; Akhil Dhanesh Goel; Tanisha Garg; Yogesh Kumar Jain; Manoj Kumar Gupta; Prem Singh; Jitendra Kumar Soni (PLoS ONE, 2025)
Introduction Anemia is a global health concern, affecting over 2 billion people worldwide. Rajasthan state of India launched an intensive phase initiative to combat anemia comprehensively. Objectives To assess the intensive phase anemia control “Shakti Divas” initiative of Rajasthan government through process and outcome valuation, while understanding the challenges and barriers in the implementation. Methods A state-wide mixed methods cross-sectional survey was conducted. Process evaluation was done through data collection in seven identified districts of Rajasthan. This included surveys in Anganwadi centers and government schools, and home visits for out-of-school children, pregnant and lactating women not coming to Anganwadi centres. For outcome evaluation, IFA coverage data was obtained from government web portals one-month before and six-months after the launch of initiative. 38 in-depth interviews were conducted to assess the challenges and barriers. Results Process evaluation - cross-sectional surveys conducted in 1100 Anganwadi centers serving 68,651 beneficiaries, and 1240 government schools serving 1,30,114 students, and home visits to survey 29,960 children and 18,632 pregnant women. 843 Anganwadi centers (76.6%), benefitting 68,651 people and 916 schools (73.8%) with 97,247 beneficiaries, were actively engaged in the initiative. Outcome evaluation - an overall increase in IFA coverage amongst beneficiary groups as well individual districts seen, with maximum increase amongst adolescent girls category (68.6%). Challenges were enlisted as knowledge, budgetary, supply, reporting, compliance, resource, coverage and monitoring constrains. Conclusion The paper discussed the reach and challenges of an intensified initiative to combat anemia. Similar intensified and targeted strategies may serve as the key to achieve the goal of anemia reduction thus creating a healthier future for population with similar socio-demographics in LMICs.